Special needs teachers in emergency remote teaching during the COVID-19 pandemic: the role of personal resources and teaching motivation on burnout - De Stasio, Simona; Ragni, Benedetta; Boldrini, Francesca; Paoletti, Daniela; Marchetti, Vanessa; Rappazzo, Maria Cristina; Berenguer, Carmen (Frontiers in Education, 2024)
Background This cross-sectional study explores the connections between burnout, personal resources, and teaching motivation among Italian special needs teachers (SNTs) one year following the start of the COVID-19 pandemic. It specifically seeks to determine if and how personal resources and teaching motivation can help SNTs by buffering the effects of burnout symptoms. Methods The study was conducted using a sample of 837 full-time, in-service kindergarten and primary teachers at public schools in Italy. Data were collected through self-report questionnaires, including the Copenhagen Burnout Inventory, the Santa Clara Brief Compassion Scale, the Crèche Educators Emotional Style Questionnaire, and the Autonomous Motivations for Teaching Scale. A multiple regression model was performed to assess the predictive role of personal resources and teaching motivation on the burnout of special needs teachers. Results The findings indicate that higher levels of autonomous motivation are associated with reduced burnout, specifically among special education teachers. Conversely, higher levels of negative emotion regulation strategies were linked to increased burnout, and this relationship was stronger in mainstream teachers than in special education teachers. We found no significant association between teachers’ compassion and burnout. Conclusions Our research supports the need for educational policymakers and school leaders to focus on personal resources and work-related well-being to enhance and support teachers, in particular during emergencies (e.g., the COVID-19 pandemic) and for specific groups of teachers, such as SNTs.